Risk factors for pulmonary cement embolism after percutaneous vertebroplasty and radiofrequency ablation for spinal metastases - Wang, Luqiang; Lu, Ming; Zhang, Xinxin; Zhao, Zhenguo; Li, Xiaoyang; Liu, Ting; Xu, Libin; Yu, Shengji (Frontiers in Oncology, 2023)
Objective: Pulmonary cement embolism is a rare but underestimated complication of vertebroplasty due to the relative lack of study and examination. This study aims to investigate the incidence of pulmonary cement embolism in patients with spinal metastasis who undergo PVP with RFA and to analyze the relative risk factors. Methods: A total of 47 patients were retrospectively included and classified into pulmonary cement embolism (PCE) group and non-pulmonary cement embolism (NPCE) group by comparing pre- and postoperative pulmonary CT scan images. The demographic and clinical information of the patients was obtained. Demographic data in the two groups were compared using the chi-square test for qualitative data and the unpaired t test for quantitative data. Multiple logistic regression analysis was used to identify risk factors related to pulmonary cement embolism. Results: Pulmonary cement embolism was detected in 11 patients (23.4%), and all patients were asymptomatic and followed up regularly. Risk analysis showed that multiple segments (≥3, p=0.022), thoracic vertebrae (p=0.0008), and unipedicular puncture approach (p=0.0059) were risk factors for pulmonary cement embolism. There was a high incidence of pulmonary cement embolism if bone cement leaked into the para vertebral venous plexus in the thoracic vertebra (p<0.0001). Vein leakage of cement was related to the integrity of the vertebral cortex. Conclusion: The number of involved vertebrae, lesion location, and puncture approach are independent risk factors for pulmonary cement embolism. There was a high incidence of pulmonary cement embolism if bone cement leaked into the para vertebral venous plexus in the thoracic vertebra. Surgeons should consider these factors when formulating therapeutic strategies.